Considerations in the Development of Flexible CCS Networks. (July 2017) - Wetenhall, Ben; Race, Julia; Aghajani, Hamed; Fernandez, Eva Sanchez; Naylor, Mark; Lucquiaud, Mathieu; Chalmers, Hannah
Abstract: This paper discusses considerations for the design of flexibly operated Carbon Capture and Storage (CCS) pipeline networks and is based on the findings of the Flexible CCS Network Development project (FleCCSnet), funded as part of the UK CCS Research Centre. The project considered the impact of flexibility across the whole CCS chain, as well as studying the interfaces between each element of the system; e.g. at the entry to the pipeline system from the capture plant and at the exit from the pipeline to the storage site. The factors identified are intended to allow CCS network designers to determine the degree of flexibility in the system; allowing them to react effectively to short, medium and long term variations in the flow of CO2 from capture plants and the constraints imposed on the system by CO2 injection and storage. The work of the project is reviewed in this paper which explores the flexibility of power plants operating with post combustion capture systems; quantifies the available time to store (line pack) CO2 in the pipeline as a function of pipeline size, the inlet mass flow rate and operating pressure; and explores the influence that uncertainty in injection and storage parameters have on the design of the pipeline. In addition, parameters influencing short and longer term network designs are discussed in terms of varying flow rates. Two practitioner workshops [1, 2] contributed to the direction of the project. The first workshop identified and confirmed key questions to be considered in order to understand the most likely impacts of variability in both the CO2 sources and CO2 sinks on CO2 transport system design and operation. The second workshop focused on transient issues in the pipeline and storage site. Although the case studies in the work are UK based, this work is applicable to other situations where large and small sources of CO2 are expected to be feeding into a CCS transportation system. The work is expected to inform a broad range of stakeholders and allow network designers to anticipate potential problems associated with the operation of a CCS network. For an effective design of CCS infrastructure, all of the factors that will have a substantial impact on CO2 flow will have to be analysed at an early stage to prevent possible bottle necks in the whole chain.